Roles and Responsibilities of Stakeholders in Implementing Green Tourism Practices in Restaurants: A Global Perspective on Ecological and Social Impacts - Winowatan, Wim Johannes; Suarta, I Putu; Putra Wijaya, Bayu Indra; Anneke W, Jeanny Pricilia; Ridwan, Masri (Indonesian Journal of Social and Environmental Issues (IJSEI), 2024)
Many restaurants face challenges in implementing sustainable practices due to various constraints, including financial limitations, access to eco-friendly products, and infrastructural inadequacies. Lago'Ta Cafe & Resto in Pare-Pare is no exception, despite its commendable efforts in waste management and sourcing local ingredients. This study employs a qualitative approach, combining interviews with top management, employees, and policymakers at Lago'Ta Cafe & Resto. The focus is on exploring their current sustainability practices, identifying challenges, and evaluating potential solutions. The research highlights Lago'Ta Cafe & Resto's strong commitment to sustainability through effective waste management and support for local farmers and fishermen. However, significant challenges such as financial constraints, limited availability of eco-friendly products, and infrastructural limitations pose obstacles to their sustainability efforts. To enhance its sustainability initiatives, Lago'Ta Cafe & Resto should prioritize strategic financial planning, and diversification of their supply chain to include more eco-friendly options and infrastructure improvements. Effective communication with customers about their sustainability efforts and advocacy for supportive policies are also crucial steps toward maximizing their positive impact on the environment and the local community in Pare-Pare.